Perancangan Alat Pengering Bawang Menggunakan Metode Antropometri - Harits, Hafidz; Yusianto, Rindra (Metode : Jurnal Teknik Industri, 2026)
This study aims to design an ergonomic onion dryer using an anthropometric approach to improve operator comfort and enhance the efficiency of the drying process. Traditional onion drying methods, which heavily rely on sunlight, present several drawbacks such as weather dependence and physical fatigue due to repetitive manual activities. Anthropometric measurements were conducted on several operator body dimensions, including standing height, arm span, standing elbow height, popliteal height, eye height, shoulder height, and arm reach. The collected data were analyzed using mean, standard deviation, data adequacy tests, and uniformity tests to ensure their validity as design parameters. The results indicate that all anthropometric data meet the required criteria and are suitable for determining the optimal dimensions of the dryer. Using the 50th percentile as a reference, the resulting design accommodates most users and provides ergonomic features in terms of rack height, tool dimensions, and working reach. This onion dryer design successfully improves operator comfort and supports a more efficient drying process compared to conventional manual methods. The study offers significant contributions to the development of onion processing equipment for small and medium-scale industries.